Warning Signs of Anorexia - Jacqueline Endaya; Linda Bobroff (EDIS)
“With concerns about childhood obesity on the rise, the plight of young people with eating disorders such as anorexia nervosa may not be on many people’s minds. However, according to the American Academy of Child and Adolescent Psychiatry, between 5 and 10 million people, including 1% of American teens, have an eating disorder. Anorexia nervosa, an eating disorder characterized by excessive weight loss and severely distorted body image, is one of the most common psychiatric diagnoses in young women.” This 2-page Family Album Radio transcript was written by Jacqueline Endaya and Linda Bobroff, and published by the UF Department of Family, Youth and Community Sciences, August 2012.